The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3389/fcimb.2022.814473
|View full text |Cite
|
Sign up to set email alerts
|

From Mouth to Brain: Distinct Supragingival Plaque Microbiota Composition in Cerebral Palsy Children With Caries

Abstract: Children with cerebral palsy (CP) present a higher prevalence and severity of caries. Although researchers have studied multiple risk factors for caries in CP, the role of microorganisms in caries remains one of the critical factors worth exploring. In order to explore the differences in the supragingival plaque microbiota (SPM), supragingival plaque samples were collected from 55 CP children and 23 non-CP children for 16S rRNA sequencing. Distinct SPM composition was found between CP children with severe cari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 85 publications
1
5
0
Order By: Relevance
“…Similarly, we found 96.3% incidence of periodontitis and 81.48% incidence of gingivitis in these children, which can be partly explained by their impaired oral functions, such as occlusion and swallow (25-27). Studies have observed the association of oral health with OM, including Porphyromonas, Treponema, F. nucleatum, Pseudoramibacter, Streptococcus, Prevotella as well as lactic acid-producing bacteria (7, 8, 28- Campylobacter were dental health-associated microbiota in these children (35). In line with other studies, the present study identified the accumulation of Prevotella, Fusobacterium, Neisseria, Actinomyces, Brachymonas, Streptococcus, Porphyromonas, Capnocytophaga, and Campylobacter in the OM of CPE children (7,8,26,27,35).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Similarly, we found 96.3% incidence of periodontitis and 81.48% incidence of gingivitis in these children, which can be partly explained by their impaired oral functions, such as occlusion and swallow (25-27). Studies have observed the association of oral health with OM, including Porphyromonas, Treponema, F. nucleatum, Pseudoramibacter, Streptococcus, Prevotella as well as lactic acid-producing bacteria (7, 8, 28- Campylobacter were dental health-associated microbiota in these children (35). In line with other studies, the present study identified the accumulation of Prevotella, Fusobacterium, Neisseria, Actinomyces, Brachymonas, Streptococcus, Porphyromonas, Capnocytophaga, and Campylobacter in the OM of CPE children (7,8,26,27,35).…”
Section: Discussionmentioning
confidence: 94%
“…Studies have observed the association of oral health with OM, including Porphyromonas , Treponem a, F. nucleatum , Pseudoramibacter , Streptococcus , Prevotella as well as lactic acid-producing bacteria ( 7 , 8 , 28 34 ). Liu et al found that the core caries-associated microbiota in CP children included Prevotella, Alloprevotella, Actinomyces, Catonella, and Streptobacillus, while Capnocytophaga and Campylobacter were dental health-associated microbiota in these children ( 35 ). In line with other studies, the present study identified the accumulation of Prevotella , Fusobacterium , Neisseria , Actinomyces , Brachymonas , Streptococcus , Porphyromonas , Capnocytophaga , and Campylobacter in the OM of CPE children ( 7 , 8 , 26 , 27 , 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the activities of neurons in the insular cortex changed during the tooth movement process [ 14 ], these results evidenced tooth-brain axes from activation of PDL to the neurons in the somatosensory and insular cortices. Moreover, the epidemiology association between cerebral palsy and dental caries in children also provides evidence for the presence of the tooth-brain axis [ 15 ]. Among the clinically estimated parameters for dental caries, DMFS has the highest heritability [ 15 ], making it the proper estimate for MR analysis of dental caries.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the epidemiology association between cerebral palsy and dental caries in children also provides evidence for the presence of the tooth-brain axis [ 15 ]. Among the clinically estimated parameters for dental caries, DMFS has the highest heritability [ 15 ], making it the proper estimate for MR analysis of dental caries. Result of this study was in agreement with these findings demonstrated the presence of tooth-brain regulation axes, and provided a novel tooth-brain axis from dental caries to the banks of the superior temporal sulcus cortex.…”
Section: Discussionmentioning
confidence: 99%
“…The supragingival plaque was sampled as previously described [ 27 , 28 ]. Parents were informed to ensure that the children did not brush their teeth in the morning and the night before and not to eat or drink water for 2 h before sampling.…”
Section: Methodsmentioning
confidence: 99%